Heterogeneous magnitude of immunological memory to SARS‐CoV‐2 in recovered individuals. Issue 5 (6th May 2021) - Mazzoni, Alessio; Maggi, Laura; Capone, Manuela; Vanni, Anna; Spinicci, Michele; Salvati, Lorenzo; Tekle Kiros, Seble; Semeraro, Roberto; Pengue, Luca; Colao, Maria Grazia; Magi, Alberto; Rossolini, Gian Maria; et al.
Abstract: Objective: Although the adaptive immune response to SARS‐CoV‐2 has been characterised in the acute and early convalescent phase of the disease, few studies explore whether natural infection elicits long‐lasting immunological memory in recovered individuals. In this work, we aimed to assess the maintenance of immunological memory to SARS‐CoV‐2. Methods: We evaluated the long‐term virus‐specific cellular and humoral immune response in the members of an Italian Serie A football team, who experienced a cluster of COVID‐19 in March 2020, which was strictly evaluated in the following months. Results: Our results highlight a heterogeneous magnitude of immunological memory at 5 months after infection. Indeed, 20% of the subjects displayed a weak cellular and humoral memory to SARS‐CoV‐2, suggesting that they may be at higher risk of reinfection. In addition, a history of symptomatic COVID‐19 was associated with higher levels of SARS‐CoV‐2‐reactive CD4 + T cells and specific antibody levels than in asymptomatic individuals. Conclusion: Collectively, these data demonstrate that immunity to SARS‐CoV‐2 is maintained five months postinfection even if the magnitude of response is heterogeneous among individuals. This finding suggests that some COVID‐19‐recovered subjects may benefit from vaccination. Abstract : It is currently unknown whether SARS‐CoV‐2 elicits long‐lasting immunological memory. We evaluated the long‐term immunity in an Italian football team, who experienced a cluster of SARS‐CoV‐2 infections in March 2020. Our results highlight a heterogeneous magnitude of immunological memory, suggesting that some individuals may be at risk of reinfection.